Clinical researchEffect of treadmill-based gait training on the stationary balance of elderly individuals - Monteiro, Fernanda F.; Monteiro, Wagner; Costa, Rafael V.; Costa, Maricilia S.; Correa, Joao Carlos F.; Oliveira, Claudia S. (Archives of Medical Science, 2009)
Introduction: The purpose of the present study was to compare stationary balance between a group of elderly women and young adult women using stabilometric parameters. Material and methods: Sixty elderly women with an average age of 67.6 ±4.7 years and 60 young adult women with an average age of 25.1 ±2.2 years participated in the study. A Medicapteurs quartz/piezoelectric force platform (Loran Engineering™) was used for data collection, with the sampling frequency set at 50 Hz. The experimental protocol consisted of the analysis of individuals in bipedal support, with their feet on the platform in an orthostatic position and the upper limbs in extension alongside the body. The data collection time was standardized as 20 s. Data were exported to the Microcal/Origin (version 6.0) environment for processing and interpretation. The following variables were analyzed by means of this software program: i) Center of Pressure Displacement Velocity (P) and ii) Radial Displacement of Center of Pressure (Rd). Results: The elderly individuals exhibited a significant decrease in p and Rd values under both conditions (eyes open and closed) following treadmill-based gait training. The elderly group exhibited a significant reduction in center of pressure displacement velocity under both experimental conditions (eyes open and closed) following the treadmill-based gait training. Conclusions: The results of the present study indicate that a specific exercise program, such as treadmill-based gait training, which is a dynamic activity, can improve stationary balance in successful elderly women.